1998
DOI: 10.1016/s0735-1097(98)00299-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electron beam computed tomography scanning and conventional risk factor assessment for the prediction of angiographic coronary artery disease

Abstract: Electron beam CT scanning offers improved discrimination over conventional risk factors in the identification of persons with any angiographic coronary disease or angiographic obstructive coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 20 publications
8
65
0
2
Order By: Relevance
“…This result is consistent with previous studies demonstrating that the angiographic extent and severity of CAD are directly related to CACS severity 11,12 and that angiographic stenosis severity best predicts an abnormal SPECT. 2,16 Our findings emphasize that EBCT is more sensitive than either ETT or SPECT for detecting subclinical CAD in which aggressive risk factor modification is war- …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with previous studies demonstrating that the angiographic extent and severity of CAD are directly related to CACS severity 11,12 and that angiographic stenosis severity best predicts an abnormal SPECT. 2,16 Our findings emphasize that EBCT is more sensitive than either ETT or SPECT for detecting subclinical CAD in which aggressive risk factor modification is war- …”
Section: Discussionsupporting
confidence: 92%
“…It is unlikely, however, that studying a larger population with CACS Յ100 would have altered our results because these individuals generally have insignificant CAD by angiography. 11,12,14 Another issue is whether our results vary with subject age. We observed similar correlations between SPECT and EBCT when individuals were dichotomized at 50 years of age; analysis by decade of life would require a larger sample size.…”
Section: Study Limitationsmentioning
confidence: 88%
See 2 more Smart Citations
“…10 The measurement of coronary calcification by EBCT is a more direct approach for noninvasively measuring the extent of coronary artery disease. 11 Previous studies have shown that coronary artery calcification is related to the extent of coronary atherosclerosis and is greater in patients with myocardial infarction. 12,13 Coronary artery calcification increases with age in both sexes and is substantially greater in men than in women, especially in the younger age groups.…”
mentioning
confidence: 99%